2023
DOI: 10.3390/ijms24043326
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of New Potential Inflammatory Markers in Patients with Nonvalvular Atrial Fibrillation

Abstract: Atrial fibrillation (AF), the most common arrhythmia in clinical practice, is associated with an increase in mortality and morbidity due to its high potential to cause stroke and systemic thromboembolism. Inflammatory mechanisms may play a role in the pathogenesis of AF and its maintenance. We aimed to evaluate a range of inflammatory markers as potentially involved in the pathophysiology of individuals with nonvalvular AF (NVAF). A total of 105 subjects were enrolled and divided into two groups: patients with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 46 publications
0
3
0
1
Order By: Relevance
“…Similarly, Reis and coworkers studied 105 patients with nonvalvular atrial fibrillation, looking for relevant inflammatory biomarkers [7]. Through cytometric bead array and multiplex immunoassay, they confirmed the correlation between atrial fibrillation and plasmatic levels of IL-6, IL-10 and TNF, while discovering a new potential inflammatory marker, i.e., interferon-gamma-induced protein (IP-10).…”
Section: A Commemorative Issue In Honour Of Rudolf Virchowmentioning
confidence: 88%
“…Similarly, Reis and coworkers studied 105 patients with nonvalvular atrial fibrillation, looking for relevant inflammatory biomarkers [7]. Through cytometric bead array and multiplex immunoassay, they confirmed the correlation between atrial fibrillation and plasmatic levels of IL-6, IL-10 and TNF, while discovering a new potential inflammatory marker, i.e., interferon-gamma-induced protein (IP-10).…”
Section: A Commemorative Issue In Honour Of Rudolf Virchowmentioning
confidence: 88%
“…The PPI network analysis indicated that TNF and IL6 were key genes, cellular response to chemical stress and response to oxidative stress were key biological processes. The relationship between IL6, TNF and AF had been validated [51][52] and that pointed that the mechanism of C-C,N,S treating AF maybe related to in ammation. Then the gene speci c expression analysis provided a possibilities that C-C,N,S can regulate the in ammation occurred in cardiac myocytes, adipocytes and endothelial which maybe generated by liver diseases and heart diseases [53][54][55] .…”
Section: Discussionmentioning
confidence: 99%
“…These mechanisms prolong transient calcium refractoriness and promote arrhythmogenic and spatially discordant atrial alternans. The involvement of circulating autoantibodies against M2-muscarinic acetylcholine receptors (anti-M2-R) in AF has been studied in preclinical models [6] and in humans as The involvement of circulating autoantibodies against M2-muscarinic acetylcholine receptors (anti-M2-R) in AF has been studied in preclinical models [6] and in humans as well [7]. The increased expression of tumor growth factor (TGF)-β1 and connective tissue GF (CTGF) in left atrial appendage tissues correlates with the severity of atrial fibrosis [8].…”
Section: Autoimmune Mechanisms Of Afmentioning
confidence: 99%